Evidence of hatch‐time based growth compensation in the early life history of two salmonid fishes. Issue 12 (15th December 2022) - Penney, Heather D.; Keefe, Donald G.; Perry, Robert C.; Purchase, Craig F.
Abstract: Initial body size can indicate quality within‐species, with large size increasing the likelihood of survival. However, some populations or individuals may have body size disadvantages due to spatial/temporal differences in temperature, photoperiod, or food. Across‐populations, animals often have locally adapted physiology to compensate for relatively poor environmental influences on development and growth, while within‐population individual behavioral adjustments can increase food intake after periods of deprivation and provide opportunities to catch up (growth compensation). Previous work has shown that growth compensation should include within‐population differences related to short growing seasons due to delayed hatch time. We tested the hypothesis that individual fish that hatch later grow faster than those that hatch earlier. The relative magnitude of such a response was compared with growth variation among populations. We sampled young of the year Arctic charr and brook trout from five rivers in northern Labrador. Daily increments from otoliths were used to back‐calculate size to a common age and calculate growth rates. Supporting the hypothesis, older fish were not larger at capture than younger fish because animals that hatched later grew faster, which may indicate age‐based growth compensation. Abstract : We posit a theoretical extension of growth compensation to include within‐population differences related to short growing seasons due to delayed hatch time. We back‐calculated growth rates of young of the year Arctic charr and brook trout from five rivers in northern Labrador. We found that older fish were not larger at capture than younger fish because animals that hatched later grew faster, which may indicate age‐based growth compensation.